Inadequate Efficacy of Remimazolam in Chinese Female Patients without Preoperative Benzodiazepine Exposure: A Report of Two Cases - Min-Lun Hsieh; Meng-Fu Lai; Kuang-I Cheng; Zhi-Fu Wu (Journal of Medical Sciences)
Remimazolam, a gamma-aminobutyric acid subtype A receptor agonist, serves as a benzodiazepine (BZD) anesthetic in monitored anesthesia care and general anesthesia. We present two cases in which patients not receiving regular BZD therapy maintained consciousness following the administration of remimazolam during monitored anesthesia care. Subsequent transition to propofol infusion successfully achieved adequate sedation. Our experience indicates that remimazolam efficacy may be influenced by factors other than prior BZD use. Variables, such as age, sex, and race, remain unclear in their impact. Alternative agents, such as propofol and ketamine, should be considered when remimazolam fails to achieve adequate sedation.